Gen Z Bijak Digital Penguatan Mental Remaja Melalui Dakwah Kreatif dan Literasi Keagamaan di Media Sosial - Nurwahidin, Muhammad; Sofia, Ari; Perdana, Dayu Rika; Diana, Siska Mega; Hermawan, Jody Setya (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2025)
The rapid growth of social media in the digital era has created both opportunities and challenges for Generation Z, particularly regarding mental health and religious literacy. As active digital users, youth are vulnerable to identity crises, social pressure, and exposure to unverified religious content. This community service program aimed to strengthen religious literacy and promote creative da’wah skills among youth to foster positive engagement in digital spaces. The activity employed a participatory-based learning approach consisting of educational webinars, creative da’wah workshops, digital religious literacy training, mentoring, and content publication. The program involved 35 youth participants from school-based Islamic communities in Lampung. The results showed an improvement in participants’ understanding of digital religious literacy, creative content-making skills, and awareness of mental health through spiritual perspectives. The program also succeeded in forming a sustainable digital da’wah youth community and producing a replicable training module. These findings indicate that creative da’wah training effectively empowers Gen Z to become digital change agents capable of promoting healthy, religious, and inspiring social media ecosystems.